2016
DOI: 10.1038/srep20758
|View full text |Cite
|
Sign up to set email alerts
|

Histological and transcriptome analyses of testes from Duroc and Meishan boars

Abstract: Meishan boars are known for their early sexual maturity. However, they exhibit a significantly smaller testicular size and a reduced proportion of Sertoli cells and daily sperm production compared with Duroc boars. The testes of Duroc and Meishan boars at 20, 75 and 270 days of age were used for histological and transcriptome analyses. Haematoxylin-eosin staining was conducted to observe histological structure of the testes in Duroc and Meishan boars at different ages. Although spermatogenesis occurred prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 55 publications
12
46
0
Order By: Relevance
“…More signi cantly DE miRNAs were detected in Meishan boars at age of 20 to 75 days than those in Duroc boars, which suggested that the testis developed at a faster rate in Meishan boars than in Duroc boars from 20 to 75 days. These ndings were consistent with those in previous study of mRNA expression data of matched samples [17]. Venn diagram showed 45 signi cantly DE miRNAs were ltered from the four pairwise comparisons (D20 vs D270, D75 vs D270, M20 vs M75, and M20 vs M270) ( Fig.…”
Section: Overview Of Small Rna Librariessupporting
confidence: 91%
“…More signi cantly DE miRNAs were detected in Meishan boars at age of 20 to 75 days than those in Duroc boars, which suggested that the testis developed at a faster rate in Meishan boars than in Duroc boars from 20 to 75 days. These ndings were consistent with those in previous study of mRNA expression data of matched samples [17]. Venn diagram showed 45 signi cantly DE miRNAs were ltered from the four pairwise comparisons (D20 vs D270, D75 vs D270, M20 vs M75, and M20 vs M270) ( Fig.…”
Section: Overview Of Small Rna Librariessupporting
confidence: 91%
“…For example, during human spermatogenesis, transcriptomic dynamics can help predict the potential key genes that regulate male gamete generation 4 ; in different boar breeds, transcriptome analyses revealed differences in the development of sexual function 5 and in yellow catfish, comparative transcriptome analyses highlighted differences in expressed genes and signalling pathways between XY and YY testes 6 . However, information related to spermatogenesis during the different developmental stages in teleosts is limited.…”
Section: Introductionmentioning
confidence: 99%
“…One of our previous studies of testis transcriptional pro le revealed numerous differentially expressed genes (DEGs) and important biological pathways were signi cantly correlated to mammalian reproduction between Meishan and Duroc boars at 20, 75, and 270 days of age [17]. It is interesting to further investigate how miRNAs are involved in regulating sexual function development by ne-turning gene expression [18].…”
Section: Introductionmentioning
confidence: 99%
“…Testis size in Chinese Meishan boars is only half that of conventional boars at maturity. In addition, Meishan boars accumulate Sertoli cells and seminiferous tubules at a more rapid rate compared with white composite boar during the rst month after birth [17,20,21]. The diameter and number of seminiferous tubules determine the onset of puberty in males [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation